Impostor's lure [large type] : a Sharpe & Donovan novel - Neggers, Carla (Neggers, Carla. Sharpe & Donovan novel., 2018)
"Master of suspense and New York Times bestselling author Carla Neggers delivers an exhilarating page-turner where the disappearance of a Federal prosecutor launches the latest high-stakes case for FBI agents Emma Sharpe and Colin Donovan. Newlyweds Emma and Colin are suspicious when prosecutor Tamara McDermott is a no-show at a Boston dinner party. Matt Yankowski, head of HIT, Emma and Colin's small, elite Boston-based team, is a friend of Tamara's, and he needs them to find her. In London, a woman who was supposed to meet Emma's art-detective grandfather to talk about forgeries is discovered near death. Her husband, who stayed behind in Boston, has vanished. The couple's connection to Tamara adds to the puzzle. As the search for Tamara intensifies, a seemingly unrelated murder leads Emma, Colin and HIT deep into a maze of misdirection created by a clever, lethal criminal who stays one step ahead of them. As Emma draws on her expertise in art crimes and Colin on his experience as a deep-cover agent, the investigation takes a devastating turn that tests the strengths of their families and friendships as well as their FBI colleagues as never before. Impostor's Lure is full of clever twists that will keep readers guessing right to the stunning conclusion this is part of "A sharpe & Donovan Novel" series."--